Implementasi Tempat Sampah Untuk Mendukung LPS Di Kantor Kelurahan Umban Sari - Mustaza Maa; Roni Novison; Jupri Yanda Zaira; Agus Wijianto; Amnur Akhyan; Fortinov Akbar Irdam (Politeknik Caltex Riau, 2026)
This community engagement initiative aims to support Lembaga Pengolahan Sampah (LPS) by implementing a segregated waste bin system at Kantor Kelurahan Umban Sari, Kecamatan Rumbai, Kota Pekanbaru. The primary objective is to provide dedicated bins for organic, inorganic, and hazardous waste (B3), thereby enhancing the operational effectiveness of the LPS and fostering an environmentally conscious culture among office personnel. The program was executed through a series of structured stages, including preliminary surveys, problem identification, waste bin design, proposal development, fabrication and installation of the bins, and educational outreach to sub-district staff. The outcomes of this initiative include the successful provision of categorized waste bins, comprehensive documentation, and public dissemination of the project. This activity serves as a prototype for community-based waste management practices and offers a replicable model for similar urban settings.